THE APPLICATION OF BLENDED LEARNING METHODS TO HELP IMPROVE REASONING POWER AND MASTERY OF EMBRYOLOGY SUBJECT MATTER - Magdalena, Marini (International Journal of Multidisciplinary Research and Literature, 2023)
Humans have different reasoning powers and mastery of the material; some are quick to respond, some are semi-quick to react, and some are slow to respond. Because each student has a different pattern of life diet, to improve reasoning power that responds quickly from an early age, they have consumed foods with protein, vitamins, and high fiber such as fruits, UHT milk, immune supplements, chicken meat, beef duck meat, buffalo meat, mutton, eggs, vegetables, nuts, salmon, wheat, and finally diligent exercise to sleep precisely at 21.00 WIB, drink 18 glasses of mineral water per day equivalent to 2 liters. With such a lifestyle and diet, the development system in the brain is getting better to receive various information from anywhere and quickly. The blended Learning method is very appropriate to use in Learning. There are offline meetings (face-to-face), online meetings (zoom meetings), and outing classes where, with these three methods, students will be energized in varied Learning